Возможности и перспективы применения информационного подхода к изучению социальной реальности - Бердник, Е.А. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2009)
У статті розглянута історія наукового осмислення феномену інформації та становлення інформаційної методології дослідження суспільних процесів, проаналізовано можливості та перспективи застосування інформаційного підходу до вивчення соціальної дійсності. The consequence of the phenomenon “information” comprehension in the scientific works and, as well, the development of the research informational methodology of social processes have been considered in the present article. The advantages and perspectives of the informational approach application in studying the social reality have been analyzed.
Бердник Екатерина Александровна - преподаватель кафедры методов социологических исследований Харьковского национального университета имени В.Н. Каразина
Keywords: информация; информационный подход; информационные факторы динамики социальных процессов